Perlindungan Hukum Bagi Para Pihak Dalam Proses Verzet Terhadap Putusan Verstek - Eliza Yuniar; Sidi Ahyar Wiraguna (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study is motivated by the need to ensure balanced legal protection for parties involved in verzet processes against verstek decisions within civil procedural law, especially amid the digitization of the judiciary. The objective is to analyze the legal position of the parties and evaluate the effectiveness of the verzet mechanism in guaranteeing proportional legal protection. The research adopts a normative juridical type with a literature review method. The population comprises legislation, procedural law doctrines, and court decisions relevant to verzet and verstek in Indonesia. Selected samples are purposive documents based on relevance. Data instruments include primary and secondary legal documents analyzed using qualitative descriptive techniques through comparative and synthetic textual analysis. The findings reveal verzet as a crucial instrument to protect defendants’ rights; however, its effectiveness remains constrained by administrative and technical challenges in notification and electronic court system implementation. The conclusion emphasizes the need for procedural law reform, improved human resource capacity, and technological infrastructure to enhance verzet’s functionality in the future.